Prescription Pattern of Corticosteroids in Zanjan, Iran: Corticosteroid Prescription in Iran - Rouhollah Bahmani,; Ghazaal Moghaddam,; Maryam Noubarani, (Iranian Journal of Pharmaceutical Sciences, 2016)
The aim of the present study was to provide a clear picture of the prescribing pattern of corticosteroids in Zanjan, Iran. A retrospective and cross-sectional study was conducted to describe the pattern of corticosteroids prescription at Beheshti pharmacy (Zanjan, Iran) over a period of six months between March 21 and September 22, 2013. Descriptive analyses were stratified by gender, age, type of prescribed corticosteroid and rout of administration. Separate analyses were performed to determine the most common indications leading to the prescription of injection dexamethasone. Corticosteroids were prescribed mostly (74.56%) as injection. The overall corticosteroid prescribing rate was 25.73%; 55.86%, and 44.14% in females and males, respectively. Corticosteroids were prescribed frequently for adults in both males and females. In young and middle-aged women, corticosteroids were prescribed substantially higher than in men of the same age. Dexamethasone as the most prescribed corticosteroid in both male and females was mostly prescribed for respiratory bacterial infections. The current study grows the knowledge about the use of corticosteroids in Iran and suggests more attempts to reduce corticosteroids prescription. Educational interventions to promote hygiene in the society could improve rational use of corticosteroids.